Analysis of Financial Performance in SOE Building Construction Sub-Sectors Listed on The Indonesia Stock Exchange for the 2017-2021 Period - La Ode Muh. Agung Setiawan; Ahmad Ali; Anwar Anwar (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The purpose of this study is to determine the financial performance of SOEs in the building construction sub-sector listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is descriptive research, with the location of the research at the STIEM Bongaya Makassar Investment Gallery to obtain data on the company's financial statements and visit the www.idx.co.id page to get supporting data. The research was conducted using financial ratio analysis techniques. The object of this study is a state-owned enterprise engaged in the building construction sub-sector that has gone public. The data used comes from secondary sources in the form of company financial statements. In this study, liquidity, solvency, activity, profitability, and market value ratios were used as analytical tools. This study used four state-owned enterprises in the building construction sub-sector that conducted stock offerings on the Indonesia Stock Exchange between 2017-2021 as samples. The results of the study as a whole show that based on the calculations and analysis carried out on the overall ratio, PT. Pembangunan Perumahan (Persero) Tbk. and PT Wijaya Karya (Persero) Tbk. are companies with a better level of financial performance compared to state-owned enterprises in other building construction sub-sectors.